2020
DOI: 10.1002/ijc.32881
|View full text |Cite
|
Sign up to set email alerts
|

Comparative performance evaluation of different HPV tests and triaging strategies using self‐samples and feasibility assessment of thermal ablation in ‘colposcopy and treat’ approach: A population‐based study in rural China

Abstract: Human papillomavirus (HPV) test, self-sampling and thermal ablation for cervical intraepithelial neoplasia (CIN) have been developed separately to increase screening coverage and treatment compliance of cervical cancer screening programmes. A large-scale study in rural China screened 9,526 women with their combinations to explore the optimal cervical cancerscreening cascade in the real-world. Participants received careHPV and polymerase chain reaction (PCR) HPV tests on selfcollected samples. Women positive on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 24 publications
2
58
0
Order By: Relevance
“…These findings suggested that the accessibility of cervical screening should be improved among women with poor socio-demographic status. Developing an outreach, low-cost, and easily accessible screening and treatment method could be helpful to screening promotion, as Zhao et al did in rural China [22].…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested that the accessibility of cervical screening should be improved among women with poor socio-demographic status. Developing an outreach, low-cost, and easily accessible screening and treatment method could be helpful to screening promotion, as Zhao et al did in rural China [22].…”
Section: Discussionmentioning
confidence: 99%
“…Strategies that reduce the number of visits should be also considered. For example, 'colposcopy and treat' approach, combining colposcopy and treatment with thermal ablation of the cervical abnormalities in a single visit, provides a promising algorithm to improve patients' compliance [49][50][51]. Implementation strategies of this alternative approach should be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The recent strategic document on the WHO call to elimination of cervical cancer has highlighted the necessity of implementing such an approach with particular attention to ensure treatment of all the screen detected precancers 5 . Using a colposcope to triage the HPV‐positive women and to guide immediate treatment has the dual advantage of reducing overtreatment and ensuring high compliance to treatment 6 . Treatment of the colposcopically suspected lesions in HPV‐positive women without further histopathologic verification (“colposcopy and treat”) is an effective measure to reduce the number of clinic visits and improve program efficiency 7 .…”
Section: Introductionmentioning
confidence: 99%